Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5455/msm.2012.24.29-33
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Related Morbidity among Geriatric Population of Eastern India

Abstract: Objectives:To assess the prevalence of hypertension among geriatric population and to find out its association with socio demographic parameters, non communicable diseases and level of daily activities.Methodology:Community based cross sectional study was conducted among geriatric population of Tarakeswar town, India. 402 persons were selected from total 2258 elderly persons by systematic random sampling and data was collected using pretested questionnaire followed by physical examination. Data was analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The studies from other parts of India have shown a comparatively higher prevalence of hypertension and diabetes. [ 23 24 25 ] The prevalence of poor vision and hearing impairment were also higher among the geriatric population. [ 26 ] The data regarding co-morbidity among the aged was self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…The studies from other parts of India have shown a comparatively higher prevalence of hypertension and diabetes. [ 23 24 25 ] The prevalence of poor vision and hearing impairment were also higher among the geriatric population. [ 26 ] The data regarding co-morbidity among the aged was self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Moreover, a study done in Kolkata, eastern India among the elderly in urban areas reported prevalence of 53.5%. [ 15 ] The difference in prevalence levels may be due to different geographical factors and may be due to differences in dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies done at eastern India it was found to be significantly associated. 16 Most common co morbidities among the study subject were found to be musculoskeletal problems. However other studies reported hypertension and vision problems as most common co morbidities.…”
Section: Discussionmentioning
confidence: 91%